Rapid Initiation of Intravenous Epoprostenol Infusion Is the Favored Option in Patients with Advanced Pulmonary Arterial Hypertension - Kimura, Mai (PLoS One, 2015)
BACKGROUND: Intravenous infusion (IVI) of epoprostenol is an effective treatment for patients with advanced pulmonary arterial hypertension (PAH). However, there is no widely accepted standard method for initiating the IVI therapy. This study evaluated the hemodynamic improvements achieved with IVI epoprostenol to determine the optimal protocol for treatment initiation. METHODS AND RESULTS: We retrospectively analyzed 42 consecutive PAH patients who underwent IVI epoprostenol in Keio University Hospital from 2001 to 2013. The study group comprised 30 women with a mean age of 34.3 ± 1.9 years. The etiology of PAH was idiopathic or heritable PAH (I/HPAH) in 38 cases, PAH associated with connective tissue disease in 3, and Eissenmenger’s syndrome in the remaining case. We divided the patients into rapid- and slow-initiation therapy groups according to the cumulative epoprostenol dose administered during the first 180 days, and compared the hemodynamic changes between the groups. The median cumulative doses were 6142 ± 165 μg/kg and 3998 ± 132 μg/kg epoprostenol, respectively. While there were no significant differences in mean pulmonary artery pressure (mPAP), pulmonary vascular resistance (PVR), or cardiac index (CI) between the groups before the IVI epoprostenol therapy, the rapid-initiation therapy group achieved significant improvements in these hemodynamic data compared with the slow-initiation therapy group (P < 0.005) at the follow-up right-heart catheterization (RHC). CONCLUSION: Rapid initiation of IVI epoprostenol therapy achieved the optimal hemodynamic improvements in patients with severe PAH.